Effects of Mobile Money on Beige Bank, Ghana - Acquah-Sam, Emmanuel; Bugre, Dorothy (European Scientific Journal, ESJ, 2018)
The motivation for this study was that, existing literature have reported on the growth of mobile money (MM) and its clientele base. However, studies on the effects of mobile money service on customers and performance of an individual bank; challenges, threats, and opportunities mobile money service presents to an individual bank are very rare to find so adding to the existing studies on the sector will help provide more insight into the operations of the sector and direct policy decisions of policy-makers, bank officials, and telecom operators. This study sought to find out how mobile money services have affected customers and performance of Beige Bank in Ghana. The research is a descriptive survey design that presents results in mean scores, frequency distribution tables, pie charts, bar graph, and Chi-square test of relationship. The study found that mobile money service had a positive effect on customers’ remittances. Also, mobile money positively influenced customers’ saving habits. Furthermore, majority of the respondents had bank accounts, mobile money accounts, and still engaged in MM transactions. Again, instead of being a threat, mobile money presents opportunities like, cross selling of products, increase in customer base through the registration of mobile money agents, and increased bank commissionIt is recommended that Beige Bank, Ghana and other banks in Ghana should focus on getting mobile agents to save and buy E-cash from them, and develop mobile phone apps which provide access to mobile money service where customers can easily transfer money between their bank accounts and their mobile money wallets.